Malta : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Malta during 1990-95. The paper presents an overview of some of the main structural policies and describes recent developments in the domestic economy. It notes that, whereas policies have favored private initiative, the government has retained a significant presence in the economy both through its direct control of resources and through an active industrial policy. The policy mix has helped to accentuate certain trends in the structure of output since 1987: in particular, the importance of services has continued to grow at the expense of manufacturing.